How competitive is Europe's labor? - Horst Siebert (Kiel Institute of World Economics (IfW), 1999)
Europe's labor is not competitiveness taking unemployment as the relevant indicator. The paper looks at other indicators such as job creation, productivity and unit labor costs and skills. It analyzes the reasons for the lack of competitiveness including a low degree of wage differentiation, the impact of the welfare state on the reservation wage and high labor costs to finance the social security system.
Keywords: J00; 330; Arbeitslosigkeit; Arbeitsmarkt; Internationaler Wettbewerb; Beschäftigung; Arbeitsproduktivität; Personalkosten; Lohnstruktur; Arbeitsmarktflexibilisierung; Europa